2021
DOI: 10.3892/ol.2021.12494
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine diphosphate suppresses liver cancer via inducing apoptosis in Wistar rats using interventional therapy

Abstract: Liver cancer ranks as the second leading cause of cancer-associated mortality worldwide. To date, neither current ablation therapy nor chemotherapy are considered ideal in improving the outcome of liver cancer. Therefore, more effective therapies for treating this devastating disease are urgently required. Interventional therapy has been used for numerous years in the treatment of different types of cancer, and is characterized by the direct delivery of anticancer drugs into the tumor. It has been reported tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These reports indicated that autophagy may also be a therapeutic approach for cancer and that inhibition of autophagy significantly promotes occurrence of apoptosis in the development of cancer. Moreover, reports indicate that cQ and interventional therapy combination may exert a synergistic effect and induce apoptosis in Wistar liver cancer rats (46,47). Similar to these results, in the present study, Sal induced apoptosis and autophagy in the human 97H liver cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…These reports indicated that autophagy may also be a therapeutic approach for cancer and that inhibition of autophagy significantly promotes occurrence of apoptosis in the development of cancer. Moreover, reports indicate that cQ and interventional therapy combination may exert a synergistic effect and induce apoptosis in Wistar liver cancer rats (46,47). Similar to these results, in the present study, Sal induced apoptosis and autophagy in the human 97H liver cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, autophagy inhibition by chloroquine (CQ) reduced liver damage in the ischemia/reperfusion model of acute phage but worsened when treatment was prolonged [ 5 ]. CQ treatment was found to have positive effects in chronic [ 6 ] and acute [ 7 , 8 ] CCl 4 models of liver failure; in addition, it prevented autoimmune hepatitis in humans [ 9 ] and inhibited liver cancer [ 10 , 11 ]. Additionally, the use of an autophagy inducer such as rapamycin mitigated liver damage in a model of nonalcoholic fatty liver disease [ 12 ] as well as in liver diseases of different etiologies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%